A Pharmacist's Role in a Dental Clinic: Establishing a Collaborative and Interprofessional Education Site - Kalin L. Johnson; Kevin T. Fuji; Joseph V. Franco; Shana Castillo; Karen O'Brien; Kimberley J. Begley (University of Minnesota Libraries Publishing, 2018)
Background: Dental patients often have comorbidities and take multiple medications, some of which could impact their dental health and treatment.  A pharmacist in a dental clinic can assist with the gathering, documentation and evaluation of a dental patient's medication history as it pertains to their dental visit and overall health.  Purpose: To develop and implement a collaborative and interprofessional education program with a pharmacist providing services in a dental school clinic.     Summary: Creighton University School of Dentistry, a student-operated dental clinic located in Omaha, Nebraska, provides dental care by student dentists, faculty and staff to the surrounding community in a learning-focused environment.  A pharmacist was incorporated into the dental clinic to create and establish an interprofessional relationship with both dental students and faculty beginning August 2014.  Pharmacy students on an ambulatory care advanced pharmacy practice experience rotation were eventually added to the team.  The pharmacy team provided medication therapy management services including disease state and medication counseling, medication reconciliation, identifying drug-related problems and dental implications of medications, and recommendations for prescribed medications.  Conclusion: The pharmacy team's presence was largely accepted by dental faculty, staff, dental students, and patients.  Pharmacists can play an important role in a dental clinic by performing thorough health and medication histories and communicating with dental and medical providers involved in a patient's care.